SMART ACCOUNTING INFORMATION SYSTEM DAN GREEN ACCOUNTING: INOVASI SISTEM INFORMASI AKUNTANSI UNTUK AKSELERASI SDGS - Raya Puspita Sari Hasibuan; Eli Safrida; Putri Syuhada; Indri Dithisari (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The rapid advancement of digital technology and the increasing demand for sustainable business practices have driven the transformation of accounting information systems toward the concept of a Smart Accounting Information System (Smart AIS) integrated with green accounting. This study aims to analyze how Smart AIS innovation, supported by technologies such as artificial intelligence, big data, and cloud-based systems, enhances the quality of accounting information while facilitating the implementation of green accounting principles to accelerate the achievement of the Sustainable Development Goals (SDGs). This research employs a quantitative approach using survey methods targeting organizations that have adopted digital-based accounting information systems. Data are analyzed using inferential statistical techniques to examine the relationships between Smart AIS quality, green accounting implementation, and their impact on corporate sustainability performance. The findings indicate that Smart AIS has a positive and significant effect on improving transparency, accountability, and the effectiveness of sustainability reporting. Furthermore, the integration of green accounting within Smart AIS enhances environmental awareness and resource efficiency within organizations. In conclusion, the integration of Smart AIS and green accounting represents a strategic innovation that can accelerate the achievement of the SDGs, particularly in promoting good governance, responsible consumption and production, and climate action. This study provides practical implications for organizations to develop adaptive, technology-driven, and sustainability-oriented accounting systems.